Analisis Air Tak Berekening (Non Revenue Water) Menggunakan Metode Neraca Air di Perumda Air Minum Tirta Giri Nata Kota Cirebon - Luthfianto, Ahmad Kuslan; Ervin Nurhayati; Dades Prinandes; Lia Amaliah (Jurnal Serambi Engineering, 2025)
Non-Revenue Water (NRW) remains a major challenge for water utilities (PDAM) in Indonesia in providing drinking water services to the public. This is reflected in the national average NRW rate in 2023, which reached 33.51%, exceeding the RPJMN target of 25%. Reducing NRW will be more effective if its indicators and components can be measured accurately. However, many PDAMs still do not fully understand the definitions or how to calculate NRW components according to international standards with a high level of confidence. This study aims to develop a water balance using the WB-EasyCalc tool to obtain values for each NRW component with a 95% confidence level, estimate potential revenue losses, and determine the Infrastructure Leakage Index (ILI). The analysis shows that the NRW level at Perumda Air Minum Tirta Giri Nata Kota Cirebon in 2024 is 33.92% with a margin of error of 1.5%. This percentage consists of 1.09% unbilled authorized consumption, 8.22% apparent losses, and 24.62% real losses. If this NRW level is not reduced, the potential revenue loss is estimated at IDR 48,752,716,594 per year. The ILI value obtained is 70, which falls into performance category D—indicating extremely high resource wastage and the need for urgent prioritization in leakage reduction programs. Therefore, active efforts are recommended in leak detection and network pressure management.